The Implementation of Accrual-Based Accounting in Regional Governments in Indonesia - Shaari Abd. Rahman; Arni Karina; Muhammad Nur; Padri Achyarsyah; Kumba Digdowiseiso (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2023)
The introduction of an accrual-based accounting system has been an important step in efforts to improve public financial governance in Indonesian regional governments. There is a lack of transparency and accountability in local government financial management which needs to be improved to optimize the functioning of public funds. The main objective of implementing accrual-based accounting is to create a more informative and accurate financial reporting system, which can help local governments make better decisions, as well as enable better monitoring of the use of public funds. This process involves establishing accrual-based accounting standards, changing the accounting system, training human resources, and changing organizational culture. The result of this implementation is a significant increase in the quality of local government financial reports. These reports are now more informative and accurate, enabling more effective monitoring, and increasing confidence in the management of public funds. Thus, the implementation of accrual-based accounting has brought a real function to public financial governance in Indonesia, ensuring public resources are applied wisely, and directing local governments in a more professional direction in financial management. This step is an important milestone in realizing a more transparent, accountable, and efficient government in Indonesia